Characterization of pregnancy outcome of women with an offspring with inborn errors of metabolism: A population-based study - Epstein Weiss, Tali; Erez, Offer; Hazan, Itai; Babiev, Amit-Shira; Staretz Chacham, Orna (Frontiers in Genetics, 2022)
Introduction: Inborn errors of metabolism (IEM) are scarce, and their diagnosis is often made after birth. This has led to the perception that most fetuses affected by these disorders do not become clinically apparent during pregnancy. Our aim was to determine the obstetrical characteristics of women with an offspring affected by IEM. Methods: This population-based retrospective cohort study included all women who delivered at the Soroka University Medical Center (SUMC) from 1988 to 2017- who met the inclusion criteria. Mothers who had an offspring with IEM were included in the study group, and those who had offsprings without IEM comprised the comparison group. Results: 388,813 pregnancies were included in the study, 184 of them were complicated by a fetus with IEM. The rate of Bedouin women was higher in the IEM affected infant than the comparison group (90.8% Vs 53.3%, p<0.001); women with a fetus who had IEM had a higher rate of polyhydramnios (7.1% Vs. 3.2%, p=0.005), HELLP Syndrome (3.3% Vs. 1.1%, P-0.014) and preterm birth (20.7% Vs. 10.1%, p<0.001); neonates with IEM had a lower mean birth weight (p<0.001), Apgar scores at 1' and 5' minutes (p<0.001), and a higher rate of fetal growth restriction (FGR) (p<0.001), postpartum death <28 days (p<0.001) and neonatal death (p<0.001) than those in the comparison group. Pregnancies with IEM fetuses were independently associated with preterm birth (OR 2.00; CI 1.4-3), polyhydramnios (OR 2.08; CI 1.17-3.71) and FGR (OR 2.24; CI 1.2-4.19). Each family of metabolic diseases is independently associated with specific pregnancy complications (i.e. Mitochondrial diseases are associated with HELLP syndrome (OR 5.6; CI 1.8-17) and lysosomal storage disease are associated with non-immune hydrops fetalis (OR 26.4; CI 3.39-206). Conclusion: This study reports for the first time an independent association of IEM with specific complications of pregnancy. This observation has clinical implications, as the identification of specific pregnancy complications in a population at risk for IEM can assist in the prenatal diagnosis of an affected fetus.